MEDIA ONLINE “MOGIGU” EFFECTIVE FOR INCREASING KNOWLEDGE ABOUT TOOTHBRUSHING ON ELEMENTARY SCHOOL STUDENTS GROBOGAN REGENCY - Joni Satria; Diyah Fatmasari (Jurnal Riset Kesehatan, 2020)
Dental caries is a dental health problem that is widely found in Indonesia. One way to improve a child's knowledge of maintaining dental and oral health is to provide dental health education on how to brush the teeth properly using appropriate and innovative tools or media. The type of research is quasi-experiment with pretest and posttest group design, sampling technique using Slovin formula. Media to increase knowledge is media online "mogigu" and offline media with a phantom. Differences between the groups in the test with the Wilcoxon and Mann Whitney tests. The results of the paired tests showed that counseling on how to brush your teeth using phantom media and using online media "mogigu" effectively increased knowledge of how to brush the teeth, a significant pretest and posttest value of p less than 0.05. The distributions in the two groups differed significantly showed that online media "mogigu" was more effective at increasing knowledge of how to brush the teeth than phantom media value p=0.000 (p less than 0.005). Media online "mogigu" more effectively improves knowledge on how to brush teeth than phantom media.